Transforming Supply Chain Management with AI, RPA, and SAP Variant Configuration: A Data-Driven Approach - Aderinokun, Aderinsola (MZ Journal of Artificial Intelligence, 2024)
This paper explores the transformative potential of integrating Artificial Intelligence (AI), Robotic Process Automation (RPA), and SAP Variant Configuration in supply chain management. By leveraging a data-driven approach, organizations can enhance operational efficiency, improve decision-making, and achieve greater customization in their supply chains. The paper highlights the benefits, challenges, and future directions of these technologies, providing a comprehensive overview for stakeholders seeking to innovate their supply chain strategies.